CONSTRUCTION OF THE MATHEMATICAL MODEL OF THE STRENGTH OF FURNITURE PANELS MADE OF GLAMINATED BEECH LAWS - Podibka , Taras (Forestry, Forest, Paper and Woodworking Industry, 2024)
It is substantiated and proposed on the basis of a system analysis to use in the technological processes of woodworking short-sized and dimensionally suitable residues in a massive form for the production of furniture boards. Furniture boards was made from beech wood, which was tested to the limit of strength during static bending. The furniture boards were made of hard-leaved species (common beech (Fagus sylvatica L.) according to the developed methodological grid of the experiment. Based on the obtained results, a mathematical (regression) model of the dependence of the strength limit during static bending σu on the consumption of glue when gluing the rails to a smooth surface was built of the joint Q(х1) and the width of the beech wood slats S(х2). The obtained model is adequate, and therefore can be used to describe the object of the study (x1) in the design of the furniture board made of beech wood does not lead to a significant increase in the strength limit during static bending σu (from 0.69 to 3.75%). Instead, the trend of the influence of the width of the beech wood slats S(x2) on the reduction of the strength limit during static bending σu is more significant (from 3.41 to 6.69%) (Fig. 3). requirements (15 MPa). According to the results of the experiment, the strength limit during static bending σu was optimized from the consumption of glue when gluing the rails to a smooth joint Q(x1) and the width of the beech wood rails S(x2) using the gradient method, as a result of which it was found that the maximum value of the limit strength during static bending σu = 21.53 MPa, taken as an absolute value, can be obtained by fixing the consumption of glue when gluing the rails to a smooth joint Q(х1) = 280 g/m2 and the width of the rails from beech wood S(х2) = 38,43 mm. It was established that the obtained results regarding the strength of the furniture boards during static bending were conditioned by the following regimes (developed practical recommendations): initial humidity of the rails - 8±2%; pressure - 80-110 bar, exposure time - 5-6 min, temperature - 88-92 ºС, glue consumption - 170-190 g/m2. In addition, the performed tests proved that the obtained panel-glued single-layer structures meet the requirements of the DSTU EN 13353:2009 standard "Wooden panels" in terms of the strength limit. Requirements"